VACCINATION EXTERNALITIES: THE CONCEPT AND APPLICATION IN PHARMACOECONOMIC STUDIES - Endarti, Dwi; Riewpaiboon, Arthorn (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Externalities, could be positive or negative effects, occur in almost all daily life including vaccination activities. This paper aimed to presents a literature review of the concept of vaccination externalities and its application in pharmacoeconomic/economic evaluation studies. Methods: The literature review was conducted to achieve the study objectives. Searching of literature used MEDLINE electronic database by PubMed interface as well as Google scholar search engine and employed a number of keywords. Results: There are three most common types of vaccination externalities, namely: Herd immunity, serotype replacement, and antibiotic resistance. Herd immunity gives positive effects to the benefit of vaccination, the opposite of that of serotype replacement; while antibiotic resistance could give either positive or negative effects to the benefit of vaccination. Most emergence of serotype replacement occurred after pneumococcal conjugate vaccine vaccination. Most of pharmacoeconomic studies of vaccination used dynamic models to capture vaccination externalities which often included only herd immunity effects. Taking herd immunity into account in pharmacoeconomic studies tends to increase the outcomes and reduce the cost; hence, the cost per outcome or incremental cost-effectiveness ratio will decrease, resulting more favorable cost-effectiveness ratio. Conclusions: Vaccination externalities might have effect on the results of pharmacoeconomic studies. Attentiveness should be made to interpret the results of pharmacoeconomic studies which potentially altered by the effect of vaccination externalities. Keywords: Vaccination externality, Herd immunity, Serotype replacement, Antibiotic resistance, Pharmacoeconomic, Dynamic model.